1984
DOI: 10.1093/infdis/150.6.883
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Titers of Antibodies to CMV in Blood Donors to the Transmission of Cytomegalovirus Infection

Abstract: Titers of antibody to cytomegalovirus (CMV) of 529 persons whose blood had been supplied to 51 selected patients who underwent open-heart surgery were determined by indirect hemagglutination (IHA) and IgM-specific indirect immunofluorescence (IFA). Twenty-eight patients showed evidence of active CMV infection after transfusion (seroconversion or a fourfold rise in titer by IHA), whereas 23 showed no serological change. Patients with active CMV infections had received, on average, a greater number of blood unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 17 publications
6
18
0
Order By: Relevance
“…These data strongly suggest that screening for anti-CMV IgM only will not prevent transmission of CMV through blood transfusions. This conclusion is supported by data from other investigators [15], who calculated that only half of the posttransfusion CMV infections would have been prevented when IgM anti-CMV-positive blood would have been excluded. The overall prevalence of CMV-specific IgM in healthy blood donors found by us (0.16%) is in agreement with one study [16] and is lower than reported by some other investigators [15,17].…”
Section: Vironostika Anti-cmvsupporting
confidence: 58%
See 1 more Smart Citation
“…These data strongly suggest that screening for anti-CMV IgM only will not prevent transmission of CMV through blood transfusions. This conclusion is supported by data from other investigators [15], who calculated that only half of the posttransfusion CMV infections would have been prevented when IgM anti-CMV-positive blood would have been excluded. The overall prevalence of CMV-specific IgM in healthy blood donors found by us (0.16%) is in agreement with one study [16] and is lower than reported by some other investigators [15,17].…”
Section: Vironostika Anti-cmvsupporting
confidence: 58%
“…This conclusion is supported by data from other investigators [15], who calculated that only half of the posttransfusion CMV infections would have been prevented when IgM anti-CMV-positive blood would have been excluded. The overall prevalence of CMV-specific IgM in healthy blood donors found by us (0.16%) is in agreement with one study [16] and is lower than reported by some other investigators [15,17]. How ever, the specificity of some tests used is questionable, whereas the IgM-ELISA used here has a very high speci ficity [18].…”
Section: Vironostika Anti-cmvsupporting
confidence: 58%
“…One of these three infants developed CMV infection which lead to serious morbidity. A recent study suggested that recently infected donors may transmit CMV more efficiently than latent infected donors [5]. We find it prudent that the prescreened blood be retested before its use.…”
Section: Discussionmentioning
confidence: 76%
“…Despite early assumptions that donations from only a small subgroup of donors can cause TT-CMV [23,24,25], traditionally all seropositive donors have been regarded as potentially infectious for at-risk patients [26]. To identify potentially infectious donors, testing the donors' urine for CMV has been suggested by Kane and colleagues [23] because CMV viruria is frequent in primarily infected donors, and urine usually contains a higher viral load than peripheral blood.…”
Section: Identification Of At-risk Donorsmentioning
confidence: 99%
“…To identify potentially infectious donors, testing the donors' urine for CMV has been suggested by Kane and colleagues [23] because CMV viruria is frequent in primarily infected donors, and urine usually contains a higher viral load than peripheral blood. Presumably more feasible for daily practice are the suggestions of testing donors for rising antibody titers or IgM antibodies [24]. Alternatively, CMV-antibody positive, but gB-antibody-negative donors or donors with low-avidity antibodies can be regarded as potentially infectious [3,19].…”
Section: Identification Of At-risk Donorsmentioning
confidence: 99%